Debate on the Initiatives of the Faculty of Theology in Debrecen. The Theological Education Designed by Sándor Csikesz and Imre Révész - Dániel TÓTH-GYÓLLAI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2024)
This study examines the reform initiatives for theological education in the Reformed Church in Hungary during the early 20th century, focusing on the period between 1912 and 1940. Central to this examination are the reform plans developed by Sándor Csikesz and Imre Révész, particularly their 1937 draft aimed at unifying pastoral training. The research contextualizes these reforms within the broader historical and ecclesiastical framework, analysing the efforts and challenges faced by the Faculty of Theology in Debrecen. The study highlights the various debates and controversies sparked by the proposed reforms, particularly the opposition from other theological academies and the broader church community. Through detailed exploration of historical documents, this paper sheds light on the motivations behind the reforms, the resistance they encountered, and their lasting impact on theological education within the Hungarian Reformed Church.